Detente in Europe : real or imaginary? - Korbel, Josef (Princeton legacy library., 1972)
Josef Korbel, whose career encompasses both scholarly and diplomatic roles, presents a crisp, up-to-date survey of postwar relations between East and West. Seeking analytic, reasoned answers to the question of détente, he discusses in detail the changes in mood, policy, and practice that have occurred and are occurring. What exactly does rapprochement mean to the U.S.S.R., the U.S., East and West Europe? Is its primary objective the relaxing of tension or the achievement of security? the expansion of national interests? ideological conversion? reduction of Soviet influence? What have been th.